2022
DOI: 10.3389/feduc.2022.757874
|View full text |Cite
|
Sign up to set email alerts
|

Research Into improved Distance Learning Using VR Technology

Abstract: Practical skill-based education requires exemplary face-to-face operational teaching, and VR can enhance online distance learning, facilitating an alternative form of “face-to-face” teaching, which results in better teacher–student communication and learner self-efficacy. It also constitutes as a useful substitute for in-person teaching, and it also has a positive impact on learning effectiveness. In this study, a mixed-method approach was used, which utilized the following methodologies: a combination of quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…In overcoming the lack of face-to-face interaction, complementarily to the multimodal learning tools, Virtual Reality (VR) represents an alternative form when practical skill-based education is needed [48].…”
Section: Discussion: How Advanced Tools Can Address Identified Challe...mentioning
confidence: 99%
“…In overcoming the lack of face-to-face interaction, complementarily to the multimodal learning tools, Virtual Reality (VR) represents an alternative form when practical skill-based education is needed [48].…”
Section: Discussion: How Advanced Tools Can Address Identified Challe...mentioning
confidence: 99%
“…The purpose of teaching Chinese calligraphy is to enable students to understand the basics of calligraphy, the characteristics of calligraphic works of different periods and writing methods through the guidance of educators [30]. As art courses are improving with the times, art teachers are combining virtual reality technology with teaching Chinese Calligraphy to enhance the learning and teaching quality of Chinese Calligraphy courses through online learning media [31]. The Learning to Apply Media project significantly improved students' basic skills [32].…”
Section: B Chinese Calligraphy Instructionsmentioning
confidence: 99%
“…The results indicated that learning the target language in a VR environment was a practical intervention for developing autonomous motivation and L2 students had better attitudes towards their learning experiences. Li et al [35] evaluated the effectiveness of VR tools for students to learn 3D vectors in an introductory university physics course and students praised the value of VR tools in enhancing their learning experience and understanding of knowledge.…”
Section: Effectiveness Evaluation Of Learning Systemsmentioning
confidence: 99%